Implementation of Nusantara Islamic Values in Islamic Religious Education Learning to Strengthen the National Character of Students in SDN Giri Mukti, Bandung Regency - Imam Asrofi; Muhammad Hilmi Dwi Adani; Yulian Permana; Ellis Latifah; Dian Nurdiyah; Aisyah; Rianti Sudarisman Putri (Bulletin of Pedagogical Research, 2025)
This study aims to analyze the implementation of Islam Nusantara values in Islamic Religious Education (PAI) learning and its implications for strengthening students’ national character at SDN Giri Mukti. The study is motivated by the need for Islamic education that not only emphasizes cognitive aspects but also fosters religious and national character in a balanced manner within Indonesia’s pluralistic society. This research employed a qualitative approach with a descriptive research design. Data were collected through interviews with Islamic Religious Education teachers, classroom observations, and documentation analysis of learning materials. The findings reveal that Islam Nusantara values, including tolerance (tasamuh), moderation (tawassuth), balance (tawazun), love for the homeland (hubbul wathan), and appreciation of local culture, have been implemented in PAI learning, although not always explicitly stated. These values are integrated through structured lesson planning, religious practices, character habituation, and teachers’ role modeling. The implementation of Islam Nusantara–based PAI learning has positive implications for strengthening students’ national character, as reflected in tolerant, moderate, humanistic attitudes, as well as social awareness and national commitment. This study concludes that integrating Islam Nusantara values into Islamic Religious Education at the elementary school level is a relevant and effective strategy for developing students’ religious character while simultaneously reinforcing national values